Study of the MTHFR 677C>T Polymorphism in Children and Adolescents with Hashimoto’s Thyroiditis: An Original Case–Control Study - Savvas Kolanis; Elisavet Georgiou; Eleni P. Kotanidou; Vasiliki Rengina Tsinopoulou; Evdoxia Sapountzi; Emmanouel Hatzipantelis; Liana Fidani; Assimina Galli-Tsinopoulou (Diagnostics)
Background/Objectives: Hashimoto’s thyroiditis (HT) is the most common cause of hypothyroidism during childhood and adolescence. Children and adolescents with HT have an increased susceptibility to the development of thyroid nodules and thyroid cancer. Among the genetic causes of thyroid cancer, the 677C>T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene is also reported. This study investigated for the first time the association between the 677C>T polymorphism (rs1801133) of the MTHFR gene and HT in children and adolescents. Methods: This case–control study included 130 children and adolescents with HT and 130 healthy controls. The 677C>T polymorphism of the MTHFR gene was studied in all participants with Restriction Fragment Length Polymorphism (RFLP) methodology for genetic variance analysis. Results: Children and adolescents with HT presented approximately 2.5 times more frequently the T allele sequences (CT and TT variants) and the T alleles in total for the 677C>T polymorphism of the MTHFR gene compared to the healthy population (OR: 2.56, CI: 1.53–4.21 and OR: 2.57, CI: 1.59–4.16, respectively). Children and adolescents with HT and T allele sequences (CT and TT variants) exhibited abnormal thyroglobulin antibodies (anti-TG) two times more frequently compared to those with the wild-type (CC) sequence in the same population (OR: 2.13, CI: 1.04–4.389). Conclusions: Children and adolescents with HT showed an increased frequency of T allele sequences (CT and TT variants) and total T alleles of the 677C>T polymorphism of the MTHFR gene compared to the healthy population.